By the waters of Babylon - Mori, Arimasa, 1911-1976 (Cornell East Asia series, 2025)
"By the Waters of Babylon is a translation of Babiron no nagare no hotori nite, a memoir and travelogue by Japanese philosopher Mori Arimasa. Mori's perspective on European and Japanese culture helped shape Japan's postwar understanding of and relationship with Europe. Here, Mori reflects on his travels and the experience of living in a foreign culture"--